#TITLE_ALTERNATIVE# - FATIMA ZAHRA FIRDAUSI (NIM :10111011),
The population explosion of slug caterpillars which infested oil palm trees contributed to decreased productivity in oil palm fruit in Indonesia. The final project explained some mathematics models to control the growth of slug caterpillars by using two biological agents. The biological agents were Bacillus thuringiensis bacteria and several parasites that generally infested slug caterpillars. The derivation of the model constructed in the final project was obtained from ordinary differential equations with no-time delay. The result was two models: model I was constructed from the interaction of healthy slug caterpillars between bacteria/parasites-infected slug caterpillars and model II was constructed from the direct interaction of healthy slug caterpillars between bacteria or parasites. Both models used equilibrium point analysis. Two equilibrium points in model I showed that there was an existence of a twodiseases on slug caterpillars, but it did not decrease the growth of slug caterpillar population significantly. On the other hand, the equilibrium points of model II did not show any existence of a two-diseases on slug caterpillars, but the equilibrium points showed a decrease in the growth of slug caterpillar population. The equilibrium points which could not be analyzed analytically were done by using sensitivity analysis. Furthermore, the final project also presented the numerical simulations from both constructed models.